A multicenter study on definitive surgery for isolated hip fracture within 24 hours. Issue 1 (January 2021) - Ang, Darwin; Anglen, Jeffrey; Ziglar, Michele; Armstrong, John; Offner, Patrick; McKenney, Mark; Plurad, David; Flaherty, Stephen; Gonzalez, Ernest; Liu, Huazhi; Danish, Mary; McCormack, Gregory; et al.
Abstract : INTRODUCTION: Isolated hip fractures (IHFs) in the elderly are high-frequency, life-altering events. Definitive surgery ⩽24 hours of admission is associated with improved outcomes. An IHF process management guideline (IHF-PMG) to expedite definitive surgery ⩽24 hours was developed for a multihospital network. We report on its feasibility and subsequent patient outcomes. METHODS: This is a prospective multicenter cohort study, involving 85 levels 1, 2, 3, and 4 trauma centers. Patients with an IHF between 65 and 100 years old were studied. Four cohorts were examined: (1) hospitals that did not implement any PMG, (2) hospitals that used their own PMG, (3) hospitals that partially used the network IHF-PMG, and (4) hospitals that used the network's IHF-PMG. Multivariable logistic regression with reliability adjustment was used to calculate the expected value of observed to expected (O/E) mortality. Statistical significance was defined as p < 0.05. RESULTS: Data on 24, 457 IHF were prospectively collected. Following implementation of the IHF-PMG, overall IHF O/E mortality ratios decreased within the hospital network, from 1.13 in 2017 to 0.87 in 2018 and 0.86 in 2019. Hospitals that developed their own IHF-PMG or used the enterprise-wide IHF-PMG had the lowest inpatient O/E mortality at 0.59 and 0.65, respectively. CONCLUSION: Goal-directed IHF-PMG for definitive surgery ⩽24 hours was implemented across a large hospital network. The IHF-PMG was associated with lower inpatient mortality. LEVEL OF EVIDENCE: Therapeutic/ Care management, Level III.